A Suzaku, NuSTAR, and XMM-Newton view on variable absorption and relativistic reflection in NGC 4151 - Beuchert, Tobias; Markowitz, A. G.; Dauser, Thomas; Garcia, Javier; Keck, M. L.; Wilms, Jörn; Kadler, M.; Brenneman, L. W.; Zdziarski, A. A. (Astronomy & Astrophysics, 2017)
We disentangle X-ray disk reflection from complex line-of-sight absorption in the nearby Seyfert NGC 4151, using a suite of Suzaku, NuSTAR, and XMM-Newton observations. Extending upon earlier published work, we pursue a physically motivated model using the latest angle-resolved version of the lamp-post geometry reflection model RELXILLCP_LP together with a Comptonization continuum. We use the long-look simultaneous Suzaku/NuSTAR observation to develop a baseline model wherein we model reflected emission as a combination of lamp-post components at the heights of 1.2 and 15.0 gravitational radii. We argue for a vertically extended corona as opposed to two compact and distinct primary sources. We find two neutral absorbers (one full-covering and one partial-covering), an ionized absorber (log xi = 2 : 8), and a highly-ionized ultra-fast outflow, which have all been reported previously. All analyzed spectra are well described by this baseline model. The bulk of the spectral variability between similar to 1 keV and similar to 6 keV can be accounted for by changes in the column density of both neutral absorbers, which appear to be degenerate and inversely correlated with the variable hard continuum component flux. We track variability in absorption on both short (2 d) and long (similar to 1 yr) timescales; the observed evolution is either consistent with changes in the absorber structure (clumpy absorber at distances ranging from the broad line region to the inner torus or a dusty radiatively driven wind) or a geometrically stable neutral absorber that becomes increasingly ionized at a rising flux level. The soft X-rays below 1 keV are dominated by photoionized emission from extended gas that may act as a warm mirror for the nuclear radiation.
Keywords: galaxies: active; galaxies: nuclei; galaxies: individual: NGC4151; galaxies: Seyfert; X-rays: galaxies